2019
DOI: 10.3390/pharmaceutics11080393
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 Gene Delivery-Based Bone Regeneration in Dentistry

Abstract: Bone morphogenetic protein-2 (BMP-2) is a potent growth factor affecting bone formation. While recombinant human BMP-2 (rhBMP-2) has been commercially available in cases of non-union fracture and spinal fusion in orthopaedics, it has also been applied to improve bone regeneration in challenging cases requiring dental implant treatment. However, complications related to an initially high dosage for maintaining an effective physiological concentration at the defect site have been reported, although an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 109 publications
1
65
0
1
Order By: Relevance
“…7 Therefore, supraphysiological doses of BMP2 have been used clinically to promote bone formation; high doses of BMP2 have been associated with serious complications, including soft tissue inflammation and heterotopic ossification. [9][10][11] Therefore, given the rapid clearance of BMP2 from the body, substantial amounts of research have focused on developing more suitable biomaterials for BMP2 delivery. Many carriers and delivery systems comprised of different materials have been investigated to maintain the controlled release and improve the safety and therapeutic efficacy of BMP2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Therefore, supraphysiological doses of BMP2 have been used clinically to promote bone formation; high doses of BMP2 have been associated with serious complications, including soft tissue inflammation and heterotopic ossification. [9][10][11] Therefore, given the rapid clearance of BMP2 from the body, substantial amounts of research have focused on developing more suitable biomaterials for BMP2 delivery. Many carriers and delivery systems comprised of different materials have been investigated to maintain the controlled release and improve the safety and therapeutic efficacy of BMP2.…”
Section: Introductionmentioning
confidence: 99%
“…The carriers used for delivery are made of metals, ceramics, polymers, and composites. 5,[10][11][12][13][14][15][16][17][18][19] Poly(lactic-co-glycolic acid) (PLGA) has been the most successful polymeric biomaterial for use in controlled drug delivery systems. 16,18,20 Many PLGA delivery systems for BMP2 have shown promise for bone repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, numerous studies have confirmed that various bone growth factors, such as bone morphogenetic protein (BMP), transforming growth factor β (TGF-β), insulin-like growth factor (IGF), and platelet-derived growth factor (PDGF), play momentous roles in the process of bone regeneration. In particular, BMPs, including BMP-2, make a critical difference in the differentiation of osteogenic progenitor cells into osteoblasts and in the bone mineralization process [12]. However, the optimal dosage of BMP-2 to be used in bone regeneration has not been determined to date [13].…”
Section: Introductionmentioning
confidence: 99%
“…These lower levels result in minimal or no off-target effects when applied in vivo (Raftery et al, 2019). Nevertheless, the amount of published work in this field, using non-viral gene delivery for orthopedic regenerative medicine is limited mainly because MSCs are difficult to transfect cells and gene delivery is not easily translated especially in vivo (Lutz et al, 2008;Lee et al, 2010;Wegman et al, 2011;Park et al, 2019). Viral gene delivery methods are efficient but are expensive, are limited in insert size, can be insertionally mutagenic and sometimes are immunogenic which restricts their use (Zheng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%